Penegakan Disiplin Bagi Warga Binaan Di Lembaga Pemasyarakatan - Mustari Mustari; Herman Herman; Nurul Rahma Amanda (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
This study aims to: (1) find out whether disciplinary enforcement in Makassar Class 1 Prison has been running well and optimally. (2) find out what are the supporting factors inhibiting discipline for inmates in Makassar Class 1 Lapas. (3) find out what are the supporting factors for upholding discipline for inmates in Makassar Class 1 Lapas. The type of research used in this study is a type of qualitative research with a descriptive approach aimed at obtaining a complete and in-depth picture as well as accurate explanations related to the enforcement of discipline for inmates in correctional institutions (studies in class 1 prisons in Makassar). This research method is a type of qualitative research with data sources obtained from correctional institutions and informants consisting of Officers and Residents of Class 1 Correctional Facility Makassar. Data collection procedures used are observation, interviews, and documentation. As well as data analysis techniques used include data reduction, data presentation, and verification and drawing conclusions.